Quality of Life of Breast Cancer Patients Undergoing Chemotherapy: A Qualitative Study - Muriyati; Hamdana; Hardianti; Nurhidayah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2024)
Cancer is one of the deadliest diseases in the world. Where cancer can occur is caused by the growth of body tissue cells that are not normal. Breast cancer patients undergoing chemotherapy often experience side effects from chemotherapy which can cause a disturbed quality of life.The existence of side effects of chemotherapy on breast cancer patients and the lack of research that discusses the quality of life of cancer patients undergoing chemotherapy, so researchers are interested in conducting this study. Purpose: To analyze the biological, psychological, social and spiritual conditions of breast cancer patients undergoing chemotherapy regarding the quality of life in Bulukumba Regency. This study uses a qualitative study (phenomenology) and the number of samples is 5 respondents with the criteria of respondents are breast cancer patients undergoing chemotherapy. The data in this study were collected through in-depth interviews on selected subjects and analyzed using Thematic Analysis. Researchers found 4 themes from the results of data analysis. The themes are: (1) physical health condition, sub-themes: Lethargy, decreased appetite, disturbed sleep patterns and fatigue. (2) psychological changes, sub-themes: feelings of anxiety and worry, lack of confidence. (3) family support, sub-themes: positive support, forms of support, and coping mechanisms. (4) spiritual activities, sub-themes: worship and surrender activities. There are 4 themes obtained in this study. It is hoped that breast cancer patients undergoing chemotherapy will increase their motivation, so that their quality of life will increase.